Corpus Hippocraticum: historical source of treatment of craniomaxillofacial trauma. Issue 3 (April 2017) - Stathopoulos, P.
Abstract: The works of Hippocrates known in the Western World as the Corpus Hippocraticum have dominated medical thought and surgical practice for centuries. A substantial part of the Hippocratic Collection is dedicated to the description of injuries pertinent to Cranio-maxillofacial surgery and their management. Hippocrates has reached this level of surgical skill despite the limited pre-recorded knowledge and the restriction of post-mortem dissections.